Peningkatan Motivasi dan Hasil Belajar Tema Manusia dan Lingkungan Menggunakan Model PBL - Hari Jati; Roni Sulistiyono; Muryanto (Sangkalemo : The Elementary School Teacher Education Journal, 2022)
Classroom Action Research (CAR) is motivated by low student motivation so that it affects the learning outcomes of the human and environmental themes of fifth grade students at SDN Kemiriombo who have not reached the minimum completeness criteria (KKM). This study aims to improve motivation and learning outcomes of human and environmental themes using the Problem Based Learning (PBL) model for fifth grade students of SDN Kemiriombo in the 2021/2022 academic year. The researcher carried out the CAR in two cycles, each cycle was carried out in two meetings. The results of the research on pre-cycle action obtained that the classical completeness score was only 33.3% with an average value of 69 and 25% of students in the category of good learning motivation. At the end of the first cycle, classical completeness increased to 75% with an average value of 82 and 16.7% in the category of very good learning motivation and 58.3% in the category of good learning motivation. The study ended in the second cycle obtained 100% classical completeness with an average value of 90 and 41.7% in the very good learning motivation category and 58.3% in the good learning motivation category. Based on the results of the study, it can be concluded that the application of the Problem Based Learning (PBL) learning model can increase motivation and learning outcomes of human and environmental themes in fifth grade students of SDN Kemiriombo in the 2021/2022 academic year. Keywords: Motivation, Learning Outcomes, Problem Based Learning